(untitled) (Asian Business Research, 2017)
The study investigates the effectiveness of financial sector reforms towards the growth of Nigerian economy from 1986 to 2015 using error correction model approach. The long-run pre-estimation tests revealed that there is long-run relationship between financial sector reform and the economic growth in Nigeria. Findings from the study showed that consistent fall in real deposit rate had engineered the mobilised credit that was invested in the economy; little wonder none of the determinants coefficient was significant. The fact that the real deposit rate has the right sign though statistically insignificant shows that given an enabling environment devoid of inflation; it could encourage savings and probably economic growth. The right sign of the credit to the private sector is equally encouraging investment – proxied by ratio of private sector credit to Gross Domstic Product (GDP) which leads one to wonder where the resources have gone. The study thus recommends that an enabling environment devoid of discouraging inflation must be provided and the financial institutions must be seem to be acting also for the interest of the economy.